PRESENT TRENDS OF GOODS AND SERVICES PROMOTION ON MARKET - Natalya V. Barinova (Вестник Российского экономического университета имени Г. В. Плеханова, 2019)
The current stage of economy development is characterized by rising interest in marketing problems. One of the most important directions is studying marketing approaches both in the broadest sense and in a narrow one. The author conducted analytical review of academic literature in this direction, researched and summarized overseas and Russian experience. The article shows existing approaches to goods and services promotion and factors affecting this process. On the basis of the analysis a conclusion was drawn that today classic strategies in marketing cannot ensure high efficiency of sales, thus one of the most topical objective of present days business is the search for new marketing approaches. Academic literature analysis showed that new forms of goods and services promotion differed greatly from conventional ones and demonstrate further trend to transformation in conditions of IT technologies development and globalization. Current marketing strategies were discussed, such as crowdsourcing, advergaming, Market Marketing, virus marketing, social mediamarketing. The author shows their key advantages and drawbacks and provides examples of their use from Russian and overseas experience. Prospects of marketing strategies development were provided.